2015
DOI: 10.1016/j.crma.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

New barriers in complexity theory: On the solvability complexity index and the towers of algorithms

Abstract: This paper addresses and establishes some of the fundamental barriers in the theory of computations and finally settles the long standing computational spectral problem.Due to the barriers presented in this paper, there are many problems, some of them at the heart of computational theory, that do not fit into the classical frameworks of complexity theory. Hence, we are in need for a new extended theory of complexity, capable of handling these new issues. Such a theory is presented in this paper. Many computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(92 citation statements)
references
References 79 publications
(137 reference statements)
0
92
0
Order By: Relevance
“…Finally, in [7,8], and many of the open problems have been solved. For example, expressed informally, we have the following:…”
Section: Addendummentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in [7,8], and many of the open problems have been solved. For example, expressed informally, we have the following:…”
Section: Addendummentioning
confidence: 99%
“…An important result in [7,8] is that the SCI hierarchy does not collapse regardless of the axioms on the algorithm. This demonstrates that any theory aiming at establishing the foundations of computational mathematics will have to include the SCI hierarchy.…”
Section: The Sci Hierarchy and Smale's Programmentioning
confidence: 99%
“…Notice that for a concrete operator T , the above construction requires the knowledge of the spectrum of T , which is computationally difficult and requires, in general, three passages to limits (see the work [9] and its full version in arxiv, where the smallest number of limit procedures necessary to solve a computational problem is studied in a systematic way).…”
Section: General Theorems On Convergencementioning
confidence: 99%
“…We will refer to any arithmetic algorithm simply as an algorithm from now on. For more general concepts the reader may consult [BHNS15].…”
Section: Introductionmentioning
confidence: 99%
“…In [BHNS15] it has been shown that if Ω is the set of compact operators on a separable Hilbert space H, then there exists a sequence of algorithms Γ n : Ω → C such that Γ n (T ) → σ(T ) (in Hausdorff sense) for all T ∈ Ω, while for the set of bounded selfadjoint operators Ω = {T ∈ L(H) | T * = T } this is not possible.…”
Section: Introductionmentioning
confidence: 99%